Family-of-origin experiences and marital adjustment among married Iranian postgraduate syudents in Malaysia - Ghoroghi, Soudbeh (2012)
The purpose of this study was to examine the relationships between family-of-origin experiences and marital adjustment in a sample of married postgraduate Iranian students in Malaysia. The sample consisted of 220 married students (92 Master’s degree and 128 Doctoral degree) including 117 females and 107 males aged 25-60. Students were randomly recruited to participate in the study through their email addresses, obtained from School of Graduate Studies at Universiti Putra Malaysia. The respondents completed demographic information and two questionnaires online including Family-of-Origin Scale (FOS; Hovestadt, et al., 1985) and the Locke-Wallace Marital Adjustment Test (LWMAT; Locke & Wallace, 1959). A quantitative correlational survey design was utilized in the present study. The researcher was interested to investigate the relationship between family of origin experiences and marital adjustment. This study sought to determine the relationships of number of children and duration of marriage with marital adjustment. Additionally, the relationship between experiences in family-of-origin scale and subscales with marital adjustment was investigated. Differences of male and female married students in terms of association between family-of-origin experiences and marital adjustment were examined. Finally this study identified marital adjustment influences by family-of-origin dimensions. Data analysis, using SPSS version 19,included frequencies, percentages, mean scores, Pearson correlation, Fisher r-to-z transformation and multiple linear regression. The results indicated that there was no correlation between number of children and marital adjustment. Similarly, the correlation between duration of marriage and marital adjustment was not significant. Family-of-origin experiences were positively and significantly correlated with marital adjustment. Men and women did not show any significant difference in association between their family-of-origin experiences and marital adjustment. Finally, family-of-origin dimensions had significant influence onmarital adjustment. The result of this study established the relationship between family-of-origin experiences and marital adjustment among married postgraduate Iranian students. Therefore, it has clear implications for clinicians, family educators and counselors and couple therapists. The result of the study can benefit those who may involve in various family-related challenges such as premarital counseling, educating couples,marital separation, marital relationship quality and divorce predicting.